Discourse and Practice on the Violence in the Argentine Anarchism at the beginning of the 20th century (The Revenge of Radowitzky and Wilckens) (Palimpsesto, 2016)
In the following article, the discourse and the practice are analyzed concerning the violence of the Buenos Aires anarchists at the beginning of the 20th century, emphasizing the called "propaganda for the fact", specially the vindictive actions perpetrated by the anarchists Simon Radowintzky and Kurt Wilckens, as response to the repressive measures, implemented by the Argentinean State to face the political and social movements. This text is focus, specifically, on the conceptualization elaborated by the theoretical anarchists and the discursive justification of, theÂ above mentioned, actions in the Argentinean context, considering the tensions and the discussions that existed inside the libertarian world. Also, the devastations of the capitalist modernization in Argentina, the immigration and the “proletarización” (the transformation of the worker) in relation to the identity construction, and the popular politicization, are mentioned, emphasizing the contributions of the anarchism in the political and social struggles of the beginning of the 20th century.
Keywords: Anarchism; “propaganda por el hecho”; social violence; state repression